Terahertz electrical writing speed in an antiferromagnetic memory - Olejnik, Kamil; Seifert, Tom; Kaspar, Zdenek; Novak, Vit; Wadley, Peter; Campion, Richard P.; Baumgartner, Manuel; Gambardella, Pietro; Nemec, Petr; Wunderlich, Joerg; Sinova, Jairo; Kuzel, Petr; et al. (Science Advances, 2018)
The speed of writing of state-of-the-art ferromagnetic memories is physically limited by an intrinsic gigahertz threshold. Recently, realization of memory devices based on antiferromagnets, in which spin directions periodically alternate from one atomic lattice site to the next has moved research in an alternative direction. We experimentally demonstrate at room temperature that the speed of reversible electrical writing in a memory device can be scaled up to terahertz using an antiferromagnet. A current-induced spin-torque mechanism is responsible for the switching in our memory devices throughout the 12-order-of-magnitude range of writing speeds from hertz to terahertz. Our work opens the path toward the development of memory-logic technology reaching the elusive terahertz band.
CRIS-Team Scopus Importer:2023-03-27